OPHIOLITES FROM THE GRAMMOS-ARRENES AREA, NORTHERN GREECE: GEOLOGICAL, PALEONTOLOGICAL AND GEOCHEMICAL DATA - Nirta, Giuseppe; Bortolotti, Valerio; Chiari, Marco; Menna, Francesco; Saccani, Emilio; Principi, Gianfranco; Vannucchi, Paola (Ofioliti, 2010)
The Grammos-Arrenes ophiolites crop out between the Pindos Flysch to the East and the Meso-Hellenic basin to the West and represent the northernmost exposure of the Pindos Ophiolite belt in Greece. Field work and sampling on key outcrops of the Sub-ophiolitic Mélange provided new data on the oceanization age and on the geochemistry of the effusive products. The basalts samples show a N-MOR affinity and are associated with latest Bajocian-early Bathonian radiolarian cherts.Emplacement of the ophiolites onto the continental margin is preceded by mass flow deposition of ophiolitic material in the basins facing the advancing ophiolitic nappe. Ophiolite-bearing debris flow deposits and slide blocks are recognized in the Early Cretaceous deep water sediments of the Beotian Unit and in the upper portion of the Tertiary Pindos Flysch. The intercalations of ophiolitic material in the Beotian Flysch first, and in the Pindos Flysch, later, are interpreted as the forerunners of the Ophiolitic Nappe which derived from the Vardar Ocean to the east, and was emplaced westwards onto the Adria continental margin.The collected data allow consolidating the constraints for the timing and mechanism of ophiolite emplacement in the Pindos-Grammos area. In addition, taking into consideration the geometry of the tectonic stack in the Grammos-Arrenes area and the ages of the involved sedimentary deposits it is possible to reconstruct a geodynamic history comparable to that of the other zones studied along the Dinaric-Hellenic Chain.